Iodine activates NLRP3 inflammasomes in PBMCs of patients with autoimmune thyroiditis and regulates Th1 and Th17 cell differentiation - Ying Wu; Qingling Guo; Yongping Liu; Xun Gong; Wei Sun; Yushu Li; Chenling Fan; Weiping Teng; Zhongyan Shan (Endocrine Connections)
Objectives: Inflammasomes are associated with various autoimmune diseases. Herein, we aimed to study the occurrence of inflammasomes in peripheral blood mononuclear cells (PBMCs) from patients with autoimmune thyroiditis (AIT), and the relationship between their abundance and the inflammatory response index of AIT. Furthermore, we examined the effect of iodine on inflammasomes containing NLR family pyrin domain-containing 3 (NLRP3) and inflammasome activation of helper T (Th) cell differentiation regulation in cultured PBMCs. Methods: We collected PBMCs and serum samples from 50 patients with AIT with normal thyroid function and 50 controls matched for age and sex. In PBMCs, the mRNA and protein expressions of certain inflammasome constituents (e.g., NLRP1, NLRP3, absent in melanoma 2 (AIM2) and caspase-1), interleukin (IL)-1β and IL-18 were assessed using qRT-PCR and western blotting. Enzyme-linked immunosorbent assays (ELISAs) assessed the serum levels of IL-1β and IL-18. Flow cytometry was employed to examine NLRP3 expression on CD14+ monocytes and Th1 and Th17 cell percentages in the groups. AIT- or healthy control-derived PBMCs were stimulated using sodium iodide, with or without lipopolysaccharide (LPS) for 72 h. Results: PBMCs from patients with AIT had significantly higher levels of pro-IL-18, pro-IL-1β and NLRP3 than did the PBMCs from the healthy controls (P < 0.05). Compared with those from the controls, AIT-derived PBMCs had enhanced levels of active IL-18 and active caspase-1 p20 (P < 0.05), whereas their abundance of active IL-1β was similar (P > 0.05). In serum, the AIT group had enhanced levels of IL-18 compared with the healthy controls (P < 0.05) but had similar levels of IL-1β (P > 0.05). NLRP3 expression on CD14+ monocytes from AIT patients was significantly augmented compared with the healthy controls (P< 0.01). Significantly increased percentages of Th1 and Th17 cells were detected in AIT patients compared with those in the healthy participants (P < 0.001). Sodium iodide treatment upregulated NLRP3 expression in PBMCs during 72 h of culture (P < 0.001). The percentage of Th1 and Th17 cells in AIT patients increased in an iodine-dependent manner (P < 0.01). Iodine had no significant effect on the number of these cells in the healthy control group (P > 0.05). Conclusion: AIT-derived PBMC NLRP3 activity and expression increased. Iodine might regulate the immune and inflammatory response of patients with AIT by activating NLRP3 and promoting Th1 and Th17 cell differentiation.